The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/phm.0000000000000982
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation for Cancer Survivors

Abstract: Cancer diagnosis often substantially affects patient's physical, psychological, and emotional status. Most patients with cancer experience declining of energy, activity levels, social-cultural participation, and relationships. In addition, cancer progression and adverse effects of aggressive cancer treatment often cause debilitating pain, fatigue, weakness, joint stiffness, depression, emotional instability, limited mobility, poor nutritional status, skin breakdown, bowel dysfunction, swallowing difficulty, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In addition, advanced cancers also are associated with increasing cancer-related disability and poor functioning which require rehabilitation to improve quality of life. However, we previously reported that cancer rehabilitation is also either not available or sub-optimally delivered in developing countries [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advanced cancers also are associated with increasing cancer-related disability and poor functioning which require rehabilitation to improve quality of life. However, we previously reported that cancer rehabilitation is also either not available or sub-optimally delivered in developing countries [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportion of case fatality rates in low-and middle-income countries (LMICs) including in Indonesia is significantly higher than in high-income countries [2,3]. Several factors including demographic, socioeconomic, and healthcare system factors are associated with the higher mortality rates in LMICs [2][3][4]. In the clinical course of cancer, mortality is primarily caused by distant metastasis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our findings, cancer treatment is still perceived to focus only on diagnosis, treatment and symptom alleviation, while rehabilitation of functional and physical problems are under-recognised and undertreated. 15 This is a paradox because physical disability including upper…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, cancer treatment is still perceived to focus only on diagnosis, treatment and symptom alleviation, while rehabilitation of functional and physical problems are under-recognised and undertreated. 15 This is a paradox because physical disability including upper body issues is often a leading cause of distress among BCSs. 16 17 In our study, 20% of BCSs reported receiving no information on rehabilitation exercises, 34% had never seen an RP for treatment or education and only a minority had presurgery measurements taken of shoulder ROM and arm circumference.…”
Section: Discussionmentioning
confidence: 99%